Hyperglycemia‐Enhanced Neutrophil Extracellular Traps Drive Mucosal Immunopathology at the Oral Barrier - Qian Wang; Weimin Lin; Kexin Lei; Hui Wang; Xiaohan Zhang; Shuang Jiang; Danting Zhang; Wen Wang; Shuqin Cao; Yuyu Li; Bo Yu; Yuan Wang; et al. (Advanced Science, 2024)
Abstract Type 2 diabetes (T2D) is a risk factor for mucosal homeostasis and enhances the susceptibility to inflammation, in which neutrophils have been increasingly appreciated for their role. Here, barrier disruption and inflammation are observed at oral mucosa (gingiva) of T2D patients and mice. It is demonstrated that neutrophils infiltrate the gingival mucosa of T2D mice and expel obvious neutrophil extracellular traps (NETs), while removal of NETs alleviates the disruption of mucosal barrier. Mechanistically, gingival neutrophils released NETs are dependent of their metabolic reprogramming. Under hyperglycemic condition, neutrophils elevate both glucose incorporation and glycolysis via increased expression of GLUT1. Moreover, significantly increased levels of NETs are observed in local gingival lesions of patients, which are associated with clinical disease severity. This work elucidates a causative link between hyperglycemia and oral mucosal immunopathology, mediated by the altered immuno‐metabolic axis in neutrophil, thereby suggesting a potential therapeutic strategy.